2020
DOI: 10.1155/2020/6381637
|View full text |Cite
|
Sign up to set email alerts
|

Computerised Methodologies for Non-Invasive Angiography-Derived Fractional Flow Reserve Assessment: A Critical Review

Abstract: Fractional flow reserve is the gold standard for assessing the haemodynamic significance of intermediate coronary artery stenoses. Cumulative evidence has shown that FFR-guided revascularisation reduces stent implantations and improves patient outcomes. However, despite the wealth of evidence and guideline recommendations, its use in clinical practice remains minimal. Patient and technical limitations of FFR as well as the need for intracoronary instrumentation, use of adenosine, and increased costs have limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Compared to the traditional pressure wire-based FFR, Coronary angiography-derived FFR does not need wire placement and is adenosine-free, the total operation times are also greatly shortened ( 20 – 23 ). Using invasive FFR as standard, a number of studies have confirmed the diagnostic accuracy of at least four kinds of angiography-derived FFR ( 23 , 24 ), including one novel computational pressure-flow dynamics (CPFD) derived FFR (caFFR) developed by our team ( 23 ). Both caFFR and quantitative flow ratio (QFR) are angiography-based FFR computational products.…”
Section: Introductionmentioning
confidence: 94%
“…Compared to the traditional pressure wire-based FFR, Coronary angiography-derived FFR does not need wire placement and is adenosine-free, the total operation times are also greatly shortened ( 20 – 23 ). Using invasive FFR as standard, a number of studies have confirmed the diagnostic accuracy of at least four kinds of angiography-derived FFR ( 23 , 24 ), including one novel computational pressure-flow dynamics (CPFD) derived FFR (caFFR) developed by our team ( 23 ). Both caFFR and quantitative flow ratio (QFR) are angiography-based FFR computational products.…”
Section: Introductionmentioning
confidence: 94%
“…QFR, like all other angio‐derived FFR methods, 5 will need further study in a large cross‐section of angiographic subtypes and clinical scenarios, and, of course, coupled to outcome studies before becoming a standard of care. This study provides reassurance that QFR works for all vessel sizes and is another step toward validating angiographic FFR for everyday use.…”
Section: Methodology Company Advantages Limitationsmentioning
confidence: 99%
“…Whilst this approach has been shown to be effective in reliably predicting FFR, it requires the use of an invasive procedure. Information on this approach has been reviewed elsewhere [12]. raw CT images [13], right: the centreline of an arterial tree reconstructed using a machine-learning enhancement [5].…”
Section: Anatomical Model Of the Vasculaturementioning
confidence: 99%
“…Whilst this approach has been shown to be effective in reliably predicting FFR, it requires the use of an invasive procedure. Information on this approach has been reviewed elsewhere 12 .…”
Section: Technology and Efficacymentioning
confidence: 99%